O23 Mechanical thrombectomy using a modified ADAPT (a direct aspiration first pass technique) in a patient with m1-occlusion and concomitant mca-aneurysm. (29th August 2022) - Demerath, T; Elbaz, A; Urbach, H; Taschner, C
Abstract : The presence of aneurysms in target vessels with large vessel occlusion undergoing mechanical thrombecomy (MT) can pose a major challenge, as current recanalization techniques usually involve blind thrombus passage with microwire and/or microcatheter. According to previous literature, the prevalence of aneurysms is relatively increased in the stroke population 1 . Previous case reports and retrospective studies indicate that patients with large vessel occlusion and concomitant aneurysm of the carrier vessel should not be deprived of mechanical recanalization, but there is a relevant risk of vessel perforation with subarachnoid hemorrhage and poor clinical outcome 1 . The value of targeted techniques such as ADAPT (A Direct Aspiration first Pass Technique) 2 in this constellation is unclear to date. We present a case in which a patient with a right-sided MCA M1 occlusion (NIHSS 30) and concomitant mediabifurcation aneurysm was fully recanalized (TICI 3) using a modified ADAPT technique, without prior passage of the thrombus as previously described by Turc et al. 2 . To us, the avoidance of blind aneurysm passage by microwire and microcatheter appears to be a major advantage of the method used. Instead, the aspiration catheter was advanced via a 0.035 Terumo guide wire for proximal stabilization. Thrombus was aspirated with proximally inflated BGC and repeated imaging series up to visualization of the aneurysm neck. Thus, blind probing of the mediabifurcation including the aneurysm was avoided and even residual thrombus adjacent to the aneurysm neck was removed. The patient benefited significantly with an improvement in NIHSS from 30 to 8 during his hospital stay. We conclude that this technique represents an interesting and potentially useful method for mechanical recanalization in the presence of a concomitant aneurysm of the carrier vessel. To what extent (modified) ADAPT is superior to other methods of mechanical recanalization in this constellation should be investigated in multicenter (e.g. registry) studies. References: Zibold F, Kleine JF, Zimmer C, Poppert H, Boeckh-Behrens T. Aneurysms in the target vessels of stroke patients subjected to mechanical thrombectomy: prevalence and impact on treatment. J Neurointerv Surg . 2016 Oct;8 (10):1016–20. doi: 10.1136/neurintsurg-2015-012079. Epub 2015 Nov 13. PMID: 26566879. Turk AS, Spiotta A, Frei D, Mocco J, Baxter B, Fiorella D, Siddiqui A, Mokin M, Dewan M, Woo H, Turner R, Hawk H, Miranpuri A, Chaudry I. Initial clinical experience with the ADAPT technique: A direct aspiration first pass technique for stroke thrombectomy. J Neurointerv Surg . 2018 Jul;10 (Suppl 1):i20-i25. doi: 10.1136/neurintsurg-2013-010713.rep. PMID: 30037948. Detailed on-screen video footage of the procedure is available for presentation. Written informed consent was obtained from the patient (BMJ consent form).